Improving upon the working environment of informal sector workers in Ghana: The role of planning - Dina Adei; Imoro Braimah; John Victor Mensah; Anthony Acquah Mensah; Williams Agyemang-Duah (Cogent Medicine, 2021)
Abstract: The formalization of the informal sector in Ghana can never be achieved without planning the working environment of the informal sector workers. Although studies have touched on various aspects of the informal sector working environment, no review studies are available on the role of planning in the working environment of the informal sector in Ghana. The purpose of this review was to identify the working environment of informal sector workers and highlight the role of planning as a first step in formalizing the sector to improve their working environment. The study is based on descriptive and narrative content analyses of the literature on the working environment of informal sector workers and the role of planning. The analysis revealed that the working environment of the informal sector workers is hazardous, devoid of social protection, and polluted, which poses risks of injuries and diseases to workers thereby undermining their health and well-being. The poor nature of the working environment of the informal sector workers makes the social, spatial, environmental and facilitating roles of planners crucial in the informal sector. Through planning, the informal sector could be sufficiently guided to appreciate the opportunities and challenges in their working environment to find lasting solutions to the inherent health and safety problems. There is a need for government to formulate a national occupational health and safety policy and regulatory framework to regulate the informal sector.